Age group-based interventions to improve psychological outcomes in people living with HIV: A systematic review - Novianti Lailiah; Nursalam; Retno Indarwati (Faculty of Medicine, Universitas Islam Indonesia, 2023)
People living with HIV (PLWH) experience higher psychological distress than the general population. Interventions to improve PLWH’s psychological condition need to be adjusted to the their age as each age group’s cognitive abilities are different. This systematic review aims to demonstrate age group-based interventions to improve psychological outcomes in PLWH. A search on articles (2014-2022) focused on experimental studies was conducted on Scopus, SAGE Journal, Science Direct, and PubMed. The searched articles tested interventions to improve psychological outcomes in PLWH and were published in English. The Joanna Briggs Institute (JBI) guidelines were used to assess their eligibility, and PRISMA diagram was used to compile the results of the search. Fifteen studies that matched the inclusion criteria were obtained, and they had experimental study designs. Several types of interventions were identified from the obtained literature. These interventions were designed according to their research subjects, and had been proven to have a significant effect on improving psychosocial conditions and quality of life in PLWH. Further research about age group-based interventions to improve psychological outcomes in PLWH is necessarily suggested. Future research is expected to be able to design interventions that focus on building resilience in individuals. The resilience is to make individuals manage their stress optimally. This may improve not only their psychosocial status but also their adherence to treatment and quality of life.